Immediate Recovery Vision for Geo-information Sector in the Context of Post 2015 Earthquake Reconstruction - B.C., Krishna; Bhatta, Ganesh Prasad; Shrestha, Suresh Man; Manandhar, Niraj; Marisini, Anil (Journal on Geoinformatics, Nepal, 2016)
The devastating Earthquake 2015 has not only caused heavy loss of human lives and properties but also destructed the base of surveying and mapping. Maps and geoinformation are the foundation for resettlement and development activities whereas Geodetic Control Network is the fundamental base for all kind of mapping activities. Accurate and reliable Geoinformation is the foundation for any Post Disaster planning, resettlement activities, Disaster Risk Reduction and all kind of development activities. The Geodetic Network is the infrastructure of the infrastructures. For any development activities, mapping is a must and that the mapping to be of sufficient accuracy, the accuracy of Geodetic Network must be ascertained. Every developmental activities, reconstruction, rehabilitation, reconciliation processes require geoinformation and other census data. Successful implementation of this programme will ensure the reduction in data redundancy and ultimately reduces the time and cost for geo spatial data production.